A cross-sectional study of individual- and poly-bullying victimization and suicidal ideation among Chinese university and high school students: the roles of hopelessness and interpersonal relationships - Zixuan Cao; Li Lu; Zi-Wei Li; Sha Lai; Zhongliang Zhou; Qing Shen; Shou Liu (International Journal for Equity in Health)
Abstract Background We aim to examine the associations between poly-bullying victimization (i.e., school-, family- and cyber-bullying ever and only) and suicidal ideation (SI) among Chinese university and high school students, and the roles of interpersonal relationships and hopelessness in the interested relationships. Methods We included 17633 participants integrating data from the 2019 mental health survey in university students in Qinghai, China (N = 5700), and the Chinese Database of Youth Health in high school students (N = 11933) in Shandong. We applied multivariate logistic regression models to explore the associations between poly-bullying victimization and SI, by gender and level of schools. Stratification analyses were conducted by levels of hopelessness and interpersonal relationships. The role of hopelessness in the relationships between poly-bullying victimization and SI in university students was evaluated by fitting mediation analyses. Results Exposure to specific forms of bullying victimization was positively associated with SI in students from both school levels. Cyberbullying victimization only was not significantly associated with SI in university students, but with significance in both female (OR: 1.70, 95% CI: 1.26–2.30) and male (OR: 2.69, 95% CI: 2.04–3.55) high school students. In university students, the association between school bullying only and SI was greater in female (OR: 2.38, 95% CI: 1.71–3.34) than males (OR: 1.33, 95% CI: 0.85–2.09); the strongest association was exhibited between the co-occurrence of family and school bullying victimization, and SI; a dose-response relationship was observed between number of victimization and SI, particularly among males. Interpersonal relationships did not significantly moderate the relationships between poly-bullying victimization and SI among university students. Hopelessness played significant mediating role in the relationships between Family + School bullying victimization and SI (14.80% mediated) in female university students, and Family + School + Cyberbullying victimization and SI (29.40%) in males. Conclusion The exploration-oriented study provided an intricate mechanism of gender-specific differences in SI related to poly-bullying victimization. Tailored, gender-sensitive interventions and support systems for adolescents and young adults should be designed and implemented.